Know-hows of Zero Tillage Technology and the Associated Constraints Experienced by the Farmers in Rice-Wheat Cropping System of Eastern Uttar Pradesh (Indian Journal of Extension Education, 2018)
The study was conducted in Deoria district of eastern Uttar Pradesh as the part of CIMMYT-CSISAproject. Out of sixteen blocks three blocks i.e. Bhatni, Bankata and Pathardewa were selected for this study as the project was implemented in these blocks. From each blockthree villages were selected purposively. From these villages fifteenzero tillage practicing farmers were selected. Hence total sample size was 135 farmers. The data were collected from through personal interview method with the help of structured interview schedule. The knowledge and constraints in practicing zero tillage technology were analyzed. The findings revealed thatmost of the farmers had knowledge about the practices of zerotillage technology. Majority of the respondents are agreed that saving of cost to the extent of 1500/acre (97.03%), need of post emergence herbicides application as necessary in zero tillage (94.81%), suitable for low lying areas (93.33%), saves water in first irrigation (92.59%) and phosphorus is placed at right depth in soil with zero till (91.85%)were the effect of the zerotillage technology. The findings also revealed that loose straw management is problem and lack of local mechanic to repair the machine was the major technical constraints faced by majority of respondents. Less coverage of mass media and lack of training on zero tillage technology to meet the information needs were observed as the most serious training and educational constraints. Higher cost of zero till machine (70.37%), lack of cooperation among farmers to share experience (67.40%) and lack of knowledge of farmers about minor adjustments of machine (80.74%) were reported as major constraints under financial, socio-psychological and extension constraints respectively.